PENGARUH LOCUS OF CONTROL, KEPRIBADIAN, DAN MOTIVASI TERHADAP KINERJA KARYAWAN (Studi pada PT. Sango Ceramics Indonesia) - Eka Novitasari; Suhana Suhana (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
This study aims to examine and analyze the effect of locus of control, personality, and motivation on employee performance at PT. Sango Ceramics Indonesia. Data was collected by distributing questionnaires with a sample of 86 respondents. The technique used for sampling in this study was saturated sampling, which took the entire population as a sample. The analysis technique used is multiple linear regression. The analytical tools used in this research are validity test, reliability test, R2 test, and T test. Based on the results of the analysis that has been done, it can be concluded that locus of control, personality, and motivation together have a positive and significant effect on employee performance.